Bridging the Software Architecture Gap. - Lindvall, Mikael; Muthig, Dirk (Computer (00189162), 2008)
This article discusses the development of the Software Architecture Visualization and Implementation (SAVE) tool. This tool is described as a program that extracts a model of software architecture as designed by the programmer, increasing the ease with which the work of subcontractors can be integrated within the framework of an application developed by multiple programmers. The SAVE utility is initially being developed for the embedded software systems that are integrated within digital cameras, automobiles, and space networks. The development of forward engineering capabilities for SAVE software, which will provide architectural guidance during the software development process, is discussed.